Observation of a case of mass diarrhea and related integrated traditional Chinese and western medicine nursing (1起群体性腹泻的病情观察及中西医护理体会) - LI Yuncui (李运翠); TANG Ling (唐玲); LI Ye (李野); WANG Liangmin (王梁敏); ZHAO Dandan (赵丹丹); QI Wenjing (綦文婧) (中西医结合护理)
This paper summarized the illness observation and nursing experience in a case of mass diarrhea. Key issues of nursing interventions for diarrhea included illness condition observation, auricular point pressing therapy, moxibustion; psychological care; diet guidance; disinfection and protection, health education and extended care. The integrated traditional Chinese and western medicine nursing is effective to relieve the diarrhea symptoms, reduce the pain degree and improve the rehabilitation of patients. (本文总结1起群体性腹泻的病情观察及护理体会, 包括病情观察、耳穴贴压、艾条灸、心理护理、饮食指导、消毒防护、健康宣教、延续性护理等措施。中西医结合护理能有效缓解患者腹泻症状, 减轻痛苦, 促进患者康复。)